Distribution of Salinity in Surface Water Surrounding Salt Mines in Non Thai and Phra Thong Kham Districts, Nakhon Ratchasima Province, Thailand: 10.32526/ennrj/22/20240042 - Terakulsatit, Bantita; Glumglomjit, Sakchai; Anuphan, Thanyalak; Nongse, Namthip (Environment and Natural Resources Journal, 2024)
Nakhon Ratchasima Province faces significant challenges due to saline soil and water, resulting from natural salt rock deposits and salt mining activities. This study investigates the physicochemical properties, salinity distribution, and surface water quality in Non Thai and Phra Thong Kham District. A total of 75 samples were collected, with 48 from Non Thai and 27 from Phra Thong Kham. The analysis focused on properties such as temperature, electrical conductivity (EC), pH, total dissolved solids (TDS), salinity, chloride, sodium, calcium, and magnesium. Water quality was assessed using standards from the Thai Department of Health and the World Health Organization. Additionally, the Sodium Adsorption Ratio (SAR) was employed to evaluate irrigation suitability, and ArcGIS 10.5 was utilized to map salinity and water quality distribution. Results indicated that surface water pH remained relatively neutral and within acceptable limits. However, salinity levels varied from 0.5 to 30 ppt, indicating brackish to saline conditions. In several areas, concentrations of salinity, sodium, and chloride exceeded standard limits. Factors such as proximity to salt mines, water flow direction, lower terrain, and smaller reservoirs were linked to increased salinity, with Phang Thiam Subdistrict in Phra Thong Kham District showing the highest levels. The SAR index further indicated that water quality in Phra Thong Kham was unsuitable for domestic use and irrigation, unlike Non Thai. Further research in other salt mine areas are essential for a deeper understanding of salinity distribution, which is crucial for assessing risks and making informed decisions to protect public health and the environment.